PENGARUH KEMAMPUAN MANAJERIAL PENGURUS DAN PARTISIPASI ANGGOTATERHADAP EFEKTIVITAS ORGANISASI KOPERASI KPRI KOPPEKA DINAS PENDIDIKAN KABUPATEN INDRAGIRI HULU - Endah Dwi martuti; Gusnardi Gusnardi; Ngadlan Ngadlan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACT : Indonesia is a republic employee cooperative form of enterprise cooperative members consist of civil servants or civil servants and established in the scope of the department or agency. objectives of this study were (1) to know how to influence the manajement of the effectiveness of manajerial ability cooperative organization, (2) to know how to influence the participation of members of the cooperative organizational effectiveness. This study is done in a cooperative KPRI KOPPEKA Dinas Pendidikan Kabupaten Indragiri Hulu with a population of 134 members and determination of sample using saturated sample (census). Data collection is done by distributing questionnaires. quantitative data analysis techniques, namely the method of multiple linear regression were processed through SPSS version 19 for windows. From these results obtained by the equation Y = a + 0.243 6.045 + 0 X1, 782X2. The results of this study indicate that simultaneous, caretaker managerial capabilities (X1) and the participation of members (X2) can influence the effectiveness of cooperative organizations (Y). This is evidenced by the F test. F count> F is 70.308> 2.44. While the ability of the managerial board (X1) and the participation of members (X2) influence on the effectiveness of cooperative organizations (Y). This is evidenced by t test. Where t count caretaker managerial ability 2.720 (X1), and the participation of members of 8.962 (X2) and t table at 1.9838. This shows that t> t table. Furthermore, the value of coefficient of determination (R2) of 51.84% was obtained, indicating the managerial capability and participation of members of the board have a contribution to the effectiveness of the cooperative organization of 51.84%. While the remaining 48.16% is influenced by other factors not examined in this study.Keywords: Managerial capabilities board, member participation and effectiveness of cooperative organization